The effect of side-chain structure on copolymer-based bulk heterojunction solar cells - Chanitpa Khantha (2018)
This paper describes the synthesis and photovoltaic studies of copolymer based on benzo[1,2-b:4,5-b-]dithiophene and 2,1,3-benzothiadiazole. Bulk-heterojunction solar cells were fabricated by using chlorobenzene, and 2% chloronapthalene as a solvent additive in chlorobenzene. The copolymers as the electron donor were blended with [6,6] -phenyl-C61-butyric acid methyl ester (PC61BM) as the electron acceptor. The effect of side-chain on BDT was compared between 4,8-bis(1-pentylhexyl)benzo[1,2-b: 4,5-b-]dithiophene (C11BDT) and 4,8-bis(1-butylhexyl)benzo[1,2-b:4,5-b-] dithioph ene (C9BDT). The power conversion efficiency (PCE) was improved with the shorter side-chain. The highest PCE was found in PC9BDTBT with 2.29%. Copyright © Taylor & Francis Group, LLC.